"In Russia we were Germans, and now we are Russians." - Dilemmas of identity formation and and communication among German-Russian Aussiedler - Barbara Pfetsch (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
This paper reports preliminary findings generated by a German-Israeli research project on the production and consumption of media by and for ethnic and minority communities. It discusses questions of social integration of ethnic minorities and mass media with respect to dilemmas of identity formation and communication among German-Russian Aussiedler. In the conceptual part, it is assumed that integration must be seen as a complex process of reciprocal social exchange between minority and majority communities, in which selfdefinitions and other-definitions play a crucial role. The media enter the picture as the negotiations of group identities are based on communication in the public sphere. Mass media create a social and political reality, thereby providing a reference system for both majority and minority communities. Against this background, identity politics and mass media functions are examined on the basis of focus group discussions with German-Russian Aussiedler. Identity politics among Ethnic Germans is fundamentally linked to the dilemma that, on the one hand, as full German citizens they belong to the majority society in legal terms. On the other hand, because of their cultural heritage, the experience of migration and language barriers, they feel excluded from the majority community to which they want to belong so badly. Concerning the role of mass media, we found that identity formation, as it is revealed by the orientations of Ethnic Germans, is not made an issue whatsoever in either minority media nor majority media. Not even the media produced for Russian-Germans in Germany touch on questions of identity or self-location of the minority vis a vis the majority. Instead, the minority media are full of practical cookbook-recipes of how to behave properly in a stereotypically-portrayed German society. – – Im Mittelpunkt des Beitrages stehen erste Ergebnisse eines deutsch-israelischen Forschungsprojektes über die Produktion und Rezeption von Medien durch ethnische und kulturelle Minderheiten. Die Frage der sozialen Integration ethnischer Minderheiten und die Rolle der Massenmedien in diesem Prozeß werden mit Blick auf die Dilemmas der Identitätsbildung und Kommunikation von Russlanddeutschen Aussiedlern diskutiert. Im konzeptuellen Teil des Papiers wird soziale Integration unter der Perspektive von Inklusion und Exklusion von Minderheiten diskutiert. Soziale Integration wird als komplexer Prozess gegenseitiger Austauschbeziehungen von Minderheit und Mehrheit konzipiert, in dem Prozesse der Selbstdefinition und Fremddefinition eine wesentliche Rolle spielen. Die Medien sind entscheidende Größen in diesen Aushandlungsprozessen, weil sie eine gemeinsame soziale und politische Realität herstellen und dadurch das entscheidende Referenzsystem für die öffentliche Aushandlung kultureller und ethnischer Identitäten bilden. Vor diesem Hintergrund wird die kulturelle und ethnische Identität, die Medienumwelt und die Mediennutzung russlanddeutscher Aussiedler untersucht. Empirische Basis sind sechs Gruppendiskussionen mit Russlanddeutschen in Bersenbrück und Berlin. Die Ergebnisse zeigen, daß die Gruppenidentität der Aussiedler mit dem Dilemma zusammenhängt, daß diese einerseits aufgrund ihrer deutschen Staatsangehörigkeit zur deutschen Mehrheitsgesellschaft gehören und sich andererseits wegen ihres kulturellen Erbes, der Erfahrung der Migration und Sprachproblemen ausgeschlossen, d.h. nicht als ,,richtige“ Deutsche “ akzeptiert fühlen. In bezug auf die Rolle der Medien zeigt die Studie, daß die Identitätsprobleme der Russlanddeutschen weder in den Aussiedlermedien noch in den deutschen Mehrheitsmedien auch nur annähernd repräsentiert sind. Vielmehr zeichnen sich die russischen Zeitungen für Russlanddeutsche dadurch aus, daß sie die Probleme ihrer Leser banalisieren und boulevardisieren.
Keywords: 300